Money doctors, foreign debts, and economic reforms in Latin America from the 1890s to the present - Drake, Paul W. 1944- (Scholarly Resources, 1994)
"Superb collection of readings and documents, with enlightening introduction, about foreign economic advisers' influence on Latin American governments and private sectors. Four parts address 'proconsul' period of US domination of the Caribbean (1898-1930), privatization and Kemmerer missions to Latin America (1917-31), IMF stabilization programs, and 'Import Substitution and the New Academics.'"--Handbook of Latin American Studies, v. 57.